A history of interior design - Pile, John.; Gura, Judith (London, United Kingdom : Laurence King Publishing, Ltd., 2013)
This classic reference presents the history of interior design from prehistory to the present. Exploring a broad range of design styles and movements, this revised and expanded edition includes coverage of non-Western design and vernacular interior architecture and features 665 photographs and drawings (color and black-and-white). A History of Interior Design is an essential resource for practicing and aspiring professionals in interior design, art history, and architecture, and general readers interested in design and the decorative arts --Amazon | A History of Interior Design tells the story of 6,000 years of domestic and public space. This fully updated fourth edition includes a completely new chapter on twenty-first-century interior design and a heavily revised chapter on the late twentieth century. Interior design is a field that includes construction, architecture, furniture, decoration, technology and product design. This one-volume history weaves together these topics in a fascinating narrative that runs from cave dwellings and temple architecture, through Gothic cathedrals and Renaissance palaces, to the grand civic spaces of the nineteenth century and the sleek interiors of modern skyscrapers. Embedded in a social and political context, detailed discussions of famous buildings, from cathedrals to Koolhaas, are interspersed with investigations of the domestic vernacular - the cottages, farmhouses, apartments and city terraces inhabited by ordinary people. The new edition of this best selling history includes over fifty new images and many previously black and white images updated to colour --Book's jacket
Includes bibliographical references and index.
Keywords: INTERIOR DECORATION